Odontogenic Fibroma - L. Sladká; M. Kyseľ; P. Kártik (Czech Dental Chamber, 2008)
In their work, the authors have addressed the matter of odontogenic fibroma.In the first section, they have been interested in the characteristics, diagnostics and treatment of odontogenic fibroma. In the second section, odontogenic fibroma involving the mandible in a case of a 25-year-old man, managed in the 1st Clinic of Dentistry in Kosice, is described. There was a swelling of the left cheek and bone-hard bulging was detected on palpation but the patient had not complained of the problems. The tumor was removed under general anesthesia and then examined histopathologically. There was no sign of recurrence six months after the operation.